Enhancement of the Concept of Charge-Energy - Hashim Jabbar, Rashid; Hadi Hilal, Israa (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of the present work is to find a relationship between mass and charge by supposing a special case (system at rest). The relation gives us the following results: Get a binding relation between the charge and energy to give us a precise interpretation for pair production (e+, e-), and prove the existence of a neutral charge for electromagnetic waves, which can also be a calculation from the wavelength; also, prove the existence of an associated wave for the particle moving charge. Finally, proving the magnetic field can be produced from the mass movement.